2007
DOI: 10.1128/jvi.00702-07
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus Evades Antiviral Signaling: Role of nsp1 and Rational Design of an Attenuated Strain

Abstract: The severe acute respiratory syndrome (SARS) epidemic was caused by the spread of a previously unrecognized infectious agent, the SARS-associated coronavirus (SARS-CoV). Here we show that SARS-CoV could inhibit both virus-and interferon (IFN)-dependent signaling, two key steps of the antiviral response. We mapped a strong inhibitory activity to SARS-CoV nonstructural protein 1 (nsp1) and show that expression of nsp1 significantly inhibited the activation of all three virus-dependent signaling pathways. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
385
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 326 publications
(400 citation statements)
references
References 51 publications
13
385
1
1
Order By: Relevance
“…However, this did not result in clinical disease, suggesting the requirement for additional adaptive changes. For example, SARS-CoV encodes at least 5 IFN antagonists, predicted to function in virulence (49)(50)(51)(52). Our model system will allow mapping of the domains in the Bat-SCoV and SARS-CoV genetic backgrounds involved in regulation of virulence in aged animals.…”
Section: Discussionmentioning
confidence: 99%
“…However, this did not result in clinical disease, suggesting the requirement for additional adaptive changes. For example, SARS-CoV encodes at least 5 IFN antagonists, predicted to function in virulence (49)(50)(51)(52). Our model system will allow mapping of the domains in the Bat-SCoV and SARS-CoV genetic backgrounds involved in regulation of virulence in aged animals.…”
Section: Discussionmentioning
confidence: 99%
“…This probably illustrates the need for a potent inhibition of IFN signaling for the life cycle of this group of viruses. Similar multiple mechanisms have also been described for other viruses such as paramyxoviruses and coronaviruses (16,29,40,54). The knowledge gained by characterizing the various mechanisms through which viruses evade IFN paves the way for the targeted attenuation of pathogenic viruses, which may be used as potential live vaccines.…”
Section: Vol 83 2009mentioning
confidence: 92%
“…Likewise, Narayanan et al showed that SARS-CoV nsp1 suppresses host gene expression in infected cells, including the expression of the type I IFN gene and ISGs like those encoding beta interferon (IFN-␤), ISG15, and ISG56 (9). It has also been reported that SARS-CoV nsp1 plays a role in the interruption of the IFN signaling pathway by decreasing the phosphorylation of STAT1 and is necessary for efficient viral growth in the human lung epithelial cell line Calu-3 (10). Mouse hepatitis virus (MHV) nsp1, a homolog of SARS-CoV nsp1, also inhibits cellular gene expression, and the viral replication of MHV devoid of nsp1 was severely attenuated in the spleen and liver of infected wild-type (WT) mice.…”
Section: Virus-induced Host Protein Shutoff Is Considered To Be a Majmentioning
confidence: 99%